Base Equation

Find the value of n n such that the following equality holds:

( n 1 ) ( n 2 ) ( 0 ) n = ( n 2 ) ( n 3 ) ( 1 ) n + 1 , n > 3 \large\overline{(n-1) (n-2) (0)}_n = \overline{(n-2) (n-3) (1)}_{n+1}, \qquad |n| > 3

Clarification : The subscript indicates number base . ( n 1 ) , ( n 2 ) , ( 0 ) , (n-1),(n-2), (0),\ldots are digits of the number.


Try more questions on Bases .


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Alex G
May 16, 2016

Relevant wiki: Number Base - Problem Solving

The numbers in the problem are equivalent to:

n 2 ( n 1 ) + n ( n 2 ) n = ( n 2 ) ( n + 1 ) 2 + ( n 3 ) ( n + 1 ) + 1 n^2(n-1)+n(n-2)n=(n-2){(n+1)}^2+(n-3)(n+1)+1

Expanding:

n 3 2 n = ( n 2 ) ( n 2 + 2 n + 1 ) + n 2 2 n 3 + 1 n^3-2n=(n-2)(n^2+2n+1)+n^2-2n-3+1

n 3 2 n = n 3 3 n 2 + n 2 2 n 2 n^3-2n=n^3-3n-2+n^2-2n-2

0 = n 2 3 n 4 0=n^2-3n-4

0 = ( n 4 ) ( n + 1 ) 0=(n-4)(n+1)

The possible answers are n = 4 n=4 and n = 1 n=-1 . n = 1 n=-1 is prohibited by the problem as the result numbers are nonsense (-3 as a digit in base -1?) The answer is therefore n = 4 n=4 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...